Improving Sustenance of Small and Marginal (Adi) Farmers through Traditional Vegetable Crops in East Siang District of Arunachal Himalaya Northeast India - TANGJANG, S.; BORANG, A.; ARUNACHALAM, A. (Indian Journal of Hill Farming, 2015)
The cropping pattern of indigenous adi tribe in East Siang district of Arunachal Pradesh, northeast India is characteristically unique, as it is based on rich traditional knowledge gained over century’s experience. In order to understand the improved rural sustenance through diversification of traditional vegetable crops of small and marginal (adi) farmers, primary information on the diversity and utilization pattern of vegetable resources were undertaken by household and field surveys during August 2010 to April 2012. Altogether, 28 vegetable crops (both cultivated as well as wild) from 22 genera and 18 families were recorded in the present study. Solanaceae with 7 species emerged as the largest family, followed by cucurbitaceae, dioscoreaceae, fabaceae and lamiaceae with 2 species each whilst the genus to species ratio for rest of the families remained 1:1. As expected, the majority of vegetables collected were eaten fresh of which, young tender leaves ranked first, followed by fruits in the preparation of vegetable dishes. Interestingly, some of the reported plants such as Carica papaya, Clerodendron colebrookianum, Perilla ocymoides, Solanum indicum, S. nigrum, S. spirale, Spilanthes paniculata and Zingiber officinale were used as traditional medicines. The present study emphasised on the traditional vegetable crops used by the adi farmers of Arunachal Pradesh, northeast India.